Mechanical and electrical properties of thermochemically cross-linked polymer carbon nanotube fibers. (December 2016) - Park, Ok-Kyung; Lee, Wonki; Hwang, Jun Yeon; You, Nam-Ho; Jeong, Youngjin; Kim, Seung Min; Ku, Bon-Cheol
Abstract: We report an effective post-treatment method to improve the mechanical and electrical properties of carbon nanotube fibers (CNTF) by using an aryl radical coupling reaction of polymers. The modified CNTF were analyzed using X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, thermogravimetric analysis (TGA) and transmission electron microscopy (TEM). The results demonstrated that chemical cross-links formed by Poly( p -iodostyrene) (PIS) inside the CNTF affected the mechanical and electrical properties. Compared with pristine CNTF, the cross-linked CNTF using PIS exhibited about 160%, 200% and 53% increased tensile strength (1.4 N/tex), elastic modulus (103 N/tex) and electrical conductivity (1480 S/cm), respectively. This post-treatment method using polymer impregnation followed by thermochemical reaction may provide a general strategy for enhancing both mechanical and electrical properties of directly spun CNTFs.